From Seoul to Copenhagen: Migrating K-Pop Cover Dance and Performing Diasporic Youth in Social Media. Issue 1 (April 2020) - Oh, Chuyun
Abstract : This article examines the practice of the Danish K-pop (Korean pop) cover dance crew CODE9 as an example of the rapid cultural exchange on the Internet that reshapes the diffusion of dance styles and ideas. CODE9 demonstrates K-pop as a "migratory dance practice, " forming a transnational dancing community with modern technology at its center. By adapting and embodying K-pop, CODE9 creates a "Thirdspace" in between reality and fantasy, between being oneself and being a Korean idol. With CODE9, K-pop moves in and out of Denmark, through the practice of watching, learning, performing, and then circulating dance online.